(untitled) (World Bulletin of Social Sciences, 2022)
Successful tourism development in the study area is linked to the natural and human geographical potentials, that can be developed and employed, according to the purpose for which the tourist seeks, including historical archaeological tourism and heritage, cultural and social tourism, which were important and effective tourism development pillars, qualify it to be desirable sites for tourists who desire these types of tourism, requires the local government in Salman district, Muthanna governorate, and the central government in Baghdad, to the protection, organization and development of historical, archaeological, heritage and social tourist sites in the study area, which suffer from the apparent neglect of tourist sites, whether archaeological sites or heritage sites, cultural or religious, can become a reliable future sector in social and economic development and alleviation of poverty and unemployment, experienced by the study area